PENYULUHAN KESEHATAN DAN PEMERIKSAAN GULA DARAH SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS PADA IBU PKK - Musa Fitri Fatkhiya; Luthfia Ayu Rachmadila; Revalina Pricilla Putryanto; Keyla Maesluha; Fatkhirotul Khusna; Vironica Anarta Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diabetes mellitus is a non-communicable disease with a continuously increasing prevalence and causes various complications. Low public knowledge regarding risk factors causes delayed diagnosis. Therefore, this community service activity aims to increase the knowledge and awareness of PKK mothers regarding diabetes mellitus while also conducting early detection through blood sugar level checks. The activity was carried out on June 15, 2026, in Kuripan Kidul Village, Pekalongan, targeting 20 PKK members. The methods used included health education through interactive lectures, discussions and questions and answers, quizzes, distribution of leaflets as educational media, and random blood sugar level checks. Evaluation of the activity was carried out based on the level of participant participation during the education and health checks. The health education program combined with simple screening in the form of blood sugar checks is an effective promotive and preventive strategy to increase public awareness of diabetes mellitus prevention. Similar activities need to be implemented continuously to support the improvement of public health.